The importance of bilingual experience in assessing bilingual advantages in executive functions - YANG, Hwajin (Institutional Knowledge at Singapore Management University, 2016)
Paap, Johnson, and Sawi (2015) contend that bilingual advantages in executive functions (EF) do not exist, and that there is no compelling evidence that a certain bilingual experience hones a specific component of EF (p. 272). We believe that this conclusion is premature, because Paap et al.'s approach was not sufficiently refined to effectively capture the real-world complexity of bilingualism. In this commentary, we draw on the adaptive control hypothesis (Green & Abutalebi, 2013) and argue that studies of bilingualism should consider specific bilingual experiences that potentially moderate bilingual advantages through substantial demand for language control (for similar commentaries, see Marzecová, 2015, and Woumans & Duyck, 2015). Based on this framework, we address two issues that have received relatively little attention in the literature and even less in this discussion forum: the interactional context of bilinguals' conversational exchanges and the age of active bilingualism.